Methodological Quality Appraisal of 27 Korean Guidelines Using a Scoring Guide Based on the AGREE II Instrument and a Web-based Evaluation - Chang, Sung-Goo (J Korean Med Sci, 2016)
This study evaluated the methodological quality of CPGs using the Korean AGREE II scoring guide and a web-based appraisal system and was conducted by qualified appraisers. A total of 27 Korean CPGs were assessed under 6 domains and 23 items on the AGREE II instrument using the Korean scoring guide. The domain scores of the 27 guidelines were as following: the mean domain score was 82.7% (median 84.7%, ranging from 55.6% to 97.2%) for domain 1 (scope and purpose); 53.4% (median 56.9%, ranging from 11.1% to 95.8%) for domain 2 (stakeholder involvement); 63.0% (median 71.4%, ranging from 13.5% to 90.6%) for domain 3 (rigor of development); 88.9% (median 91.7%, ranging from 58.3% to 100.0%) for domain 4 (clarity of presentation); 30.1% (median 27.1%, ranging from 3.1% to 67.7%) for domain 5 (applicability); and 50.2% (median 58.3%, ranging from 0.0% to 93.8%) for domain 6 (editorial independence). Three domains including scope and purpose, rigor of development, and clarity of presentation were rated at more than 60% of the scaled domain score. Three domains including stakeholder involvement, applicability, and editorial independence were rated at less than 60% of the scaled domain score. Finally, of the 27 guidelines, 18 (66.7%) were rated at more than 60% of the scaled domain score for rigor of development and were categorized as high-quality guidelines.